2000
DOI: 10.1353/aad.2012.0247
|View full text |Cite
|
Sign up to set email alerts
|

Cochlear Implants for Younger Children: A Preliminary Description of the Parental Decision Process and Outcomes

Abstract: The authors conducted a preliminary telephone interview study of a random sample of 35 parents whose children had received cochlear implants through a large-scale implant program. Parents were asked about their child's preimplant and postimplant communications skills, how they learned about implants, and how they arrived at the decision to have their child receive an implant. Results of the interviews suggest, a least for this program, that two types of decision sequences are followed. One type of parent has i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
46
1
2

Year Published

2003
2003
2020
2020

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(51 citation statements)
references
References 16 publications
2
46
1
2
Order By: Relevance
“…Parents of UNHS children diagnosed with severe/ profound HL frequently express the desire for clear speech production for their children and the diffi cult dilemma of how best to facilitate this goal (Kluwin & Stewart, 2000). This study of a homogenous cohort of UNHS identifi ed 3-and 4-year-old children diagnosed with congenital severe/profound HL, who all attended AV early intervention, who were all optimally amplifi ed with functional access to the sounds of speech within the required 20 -25 dB across all frequencies, and received CIs, if required, prior to 18 months-of-age, has shown that not only are these children capable of performing WNL on standardized tests of speech and language, but that they are capable of producing a range of 2-and 3-element initial and fi nal consonant clusters at an age commensurate with their typically-developing hearing peers.…”
Section: Resultsmentioning
confidence: 99%
“…Parents of UNHS children diagnosed with severe/ profound HL frequently express the desire for clear speech production for their children and the diffi cult dilemma of how best to facilitate this goal (Kluwin & Stewart, 2000). This study of a homogenous cohort of UNHS identifi ed 3-and 4-year-old children diagnosed with congenital severe/profound HL, who all attended AV early intervention, who were all optimally amplifi ed with functional access to the sounds of speech within the required 20 -25 dB across all frequencies, and received CIs, if required, prior to 18 months-of-age, has shown that not only are these children capable of performing WNL on standardized tests of speech and language, but that they are capable of producing a range of 2-and 3-element initial and fi nal consonant clusters at an age commensurate with their typically-developing hearing peers.…”
Section: Resultsmentioning
confidence: 99%
“…In concert, research shows that the speech production skills of deaf children also improve after implantation (Allen, Nikolopoulos, & O'Donoghue, 1998;Brown & McDowall, 1999;Ertmer & Mellon 2001). Finally, several studies have shown that spoken language development is also benefited by experience with a cochlear implant (Blamey, et al, 2001;Bollard, Chute, Popp, & Parisier, 1999;Connor, Hieber, Arts, & Zwolan, 2000;Miyamoto, Kirk, Svirsky, & Sehgal, 1999;Moeller, 2000;Tomblin, Spencer, Flock, Tyler, & Gantz, 1999).When parents are faced with the "cochlear implant decision" for their children, a driving factor in their decision is their "frustration with the child's communication skills" (Kluwin & Stewart, 2000). Improved speech perception and production skills lay the foundation for closing this communication gap; thus it is speech perception and production that are typically hailed as principal benefits of the device.…”
mentioning
confidence: 99%
“…When parents are faced with the "cochlear implant decision" for their children, a driving factor in their decision is their "frustration with the child's communication skills" (Kluwin & Stewart, 2000). Improved speech perception and production skills lay the foundation for closing this communication gap; thus it is speech perception and production that are typically hailed as principal benefits of the device.…”
mentioning
confidence: 99%
“…It is true that empirical research shows that the influence of the medical model on parents' care-related experiences and decision-making is strong (e.g. Kluwin and Stewart 2000), which is hardly surprising given that over 90% of congenitally deaf children are born to hearing parents, who 脕 as opposed to deaf parents 脕 have no experience of deafness or Deaf identity (Vaccari and Marschark 1997). But should we conclude that the distinction between medical and social/cultural-linguistic models aligns perfectly with the dividing line between hearing and deaf parents?…”
Section: Introductionmentioning
confidence: 99%